Improving Learning Outcomes in Sprint Running Using Conventional Acceleration Exercises for Grade 3 Students at State Elementary Schools 007 Kepenuhan Hulu Kecamatan Kepenuhan Hulu,Kabupaten Rokan Hulu - Nalistor Nalistor (STKIP Rokania Pasir Pangaraian, 2023)
Improving learning outcomes in sprint running by using conventional accelerated training for grade 3 students at State Elementary School 007 Kepuas Hulu, Kecepatan Hulu District, Rokan Hulu Regency. By using conventional accelerated training for sprint running, the author has formulated so that the implementation can run smoothly and prioritize success. in this research because with the implementation of this Classroom Action Research it is hoped that there will be an improvement in the learning process, especially Physical Education lessons in class 3 of SD Negeri 007 Kepuas Hulu, Kecepatan Hulu District, Rokan Hulu Regency. Using this method, the author really took into consideration the time, condition of the child, and the problems identified before carrying out classroom action research, so that it was appropriate to take action and it was proven that there was a continuous increase from cycle I, meeting I to cycle II, meeting II, then it was proven in that cycle. This method can be implemented by identifying problems, formulating problems, planning and carrying out actions, as well as evaluating so that the results achieved can improve student achievement